Desensitizing highly sensitized heart transplant candidates with the combination of belatacept and proteasome inhibition. Issue 12 (7th July 2020) - Alishetti, Shudhanshu; Farr, Maryjane; Jennings, Douglas; Serban, Geo; Uriel, Nir; Sayer, Gabriel; Vasilescu, Rodica; Restaino, Susan; Chong, Anita S.; Habal, Marlena V.
Abstract : HLA antibodies pose a significant barrier to transplantation and current strategies to reduce allosensitization are limited. We hypothesized that augmenting proteasome inhibitor (PI) based desensitization with costimulation blockade (belatacept) to mitigate germinal center (GC) responses might increase efficacy and prevent rebound. Four highly sensitized (calculated panel reactive antibody [cPRA] class I and/or II >99%, complement‐dependent cytotoxicity panel reactive antibody [CDC PRA+], C1q+) heart transplant candidates were treated with the combination of belatacept and PI therapy, which significantly reduced both class I and II HLA antibodies and increased the likelihood of identifying an acceptable donor. Three negative CDC crossmatches were achieved against 3, 6, and 8 donor‐specific antibodies (DSA), including those that were historically C1q+ binding. Posttransplant, sustained suppression of 3 of 3, 4 of 6, and 8 of 8 DSA (cases 1‐3) was achieved. Analysis of peripheral blood mononuclear cells before and after desensitization in one case revealed a decrease in naïve and memory B cells and a reduction in T follicular helper cells with a phenotype suggesting recent GC activity (CD38, PD1, and ICOS). Furthermore, a shift in the natural killer cell phenotype was observed with features suggestive of activation. Our findings support synergism between PI based desensitization and belatacept facilitating transplantation with a negative CDC crossmatch against historically strong, C1q binding antibodies. Abstract : The combination of costimulatory blockade and proteasome inhibition can be used to desensitize highly sensitized heart transplant candidates, resulting in negative crossmatches against multiple, historically strong donor‐specific antibodies, enabling transplantation and achieving sustained suppression after transplant.